KEEFEKTIFAN E-MODUL IPAS BERBASIS PROBLEM BASED LEARNING DALAM MENINGKATKAN LITERASI SAINS SISWA SEKOLAH DASAR - Rakhmatika Atmijaya; Mintarsih Arbarini; Nuni Widiarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The Effectiveness of Problem Based Learning-Based Science E-Modules in Improving Elementary School Students' Science Literacy is a study that aims to determine the effectiveness of using Problem Based Learning (PBL)-based e-modules in improving science literacy in Elementary School (SD) students in the subject of Natural and Social Sciences (IPAS). This study uses a quasi-experimental research design with a pre-test and post-test approach in two groups, namely the experimental group using PBL-based Science e-modules and the kontrol group using conventional learning methods. The subjects of the study consisted of fifth grade students of Kedungsukun 01 Elementary School, Adiwerna District, Tegal Regency. Data were collected through science literacy tests given before and after the implementation of learning, as well as observations and interviews to explore students' responses to the use of e-modules. The results of the data analysis showed that there was a significant increase in the science literacy of students using PBL-based e-modules, compared to the kontrol group. In addition, the results of the interviews showed that students were more interested and involved in PBL-based learning, which encouraged students to think critically and solve problems both independently and in groups. Based on these findings, it can be concluded that the use of PBL-based science e-modules is effective in improving elementary school students' science literacy. This study is expected to contribute to the development of more innovative and interactive science learning at the elementary school level.